Game theory : analysis of conflict - Myerson, Roger B (Harvard University Press, 1997)
Eminently suited to classroom use as well as individual study, Roger Myerson\'s introductory text provides a clear and thorough examination of the models, solution concepts, results, and methodological principles of noncooperative and cooperative game theory. Myerson introduces, clarifies, and synthesizes the extraordinary advances made in the subject over the past fifteen years, presents an overview of decision theory, and comprehensively reviews the development of the fundamental models: games in extensive form and strategic form, and Bayesian games with incomplete information. Game Theory will be useful for students at the graduate level in economics, political science, operations research, and applied mathematics. Everyone who uses game theory in research will find this book essential.
Keywords: Game Theory; Mathematics; teorie her; matematika; přírodní vědy